The Effect of Various Working Shifts on Social Wellness Among Nurses at a County Referral Hospital in Kenya - Mutua, Rosemary Mutindi; Kerochi , Atei; Jivraj , Nilufar Hassanali (International Journal of Health Sciences, 2025)
Purpose: The purpose of this study was to investigate the relationship between shift work and the social health status among nurses at the selected County Referral Hospital in Kenya. Specifically, the study aimed to assess how different work shifts affected the nurses' social well-being, so as to provide an insight that can inform strategies to improve the overall health and job performance among the nurses. Methodology: This was a descriptive cross-sectional study which was conducted among 167 nurses working in a county referral hospital in Kenya. The study adopted quantitative approach to collect data from the respondents using simple random sampling technique. Statistical package for social sciences (SPSS) version 27 software was utilized to compute descriptive statistics so as to generate mean scores for the various responses, with a mean score above 2.5 showing that the shift had a negative effect on the respondents’ social health. Results: The study findings showed that night duty and 12 hours shift had a negative effect on the respondents’ social health, with most of them stating that the shifts led to marriage instabilities, being viewed by the community as promiscuous, family strains, and also being isolated by neighbours and friends. Others included being absent in some major social activities in the family / community and lack of time to interact with family members. Unique Contribution to Theory, Policy and Practice: The study results demonstrate that night duty and the 12 hours shifts had a negative effect on the nurses’ social health. Consequently, the senior management in the institution should prioritize implementing shorter shifts (6 or 8 hours) to improve nurses’ overall wellness. There is also need to ensure a fair and structured shift rotation system to prevent prolonged night and 12-hour shifts. Mental health support, counselling services and stress management programs should also be enhanced to help nurses cope with the social effects of the long working shifts.